Pharmacokinetic herb‐drug interaction between ginger and crizotinib. Issue 9 (30th January 2019) - Revol, Bruno; Gautier‐Veyret, Elodie; Arrivé, Capucine; Fouilhé Sam‐Laï, Nathalie; McLeer‐Florin, Anne; Pluchart, Hélène; Pinsolle, Julian; Toffart, Anne‐Claire
Abstract : The use of complementary and alternative medicine at least once during or after cancer treatment has increased over the past years from an estimated 25% in the 1970s and 1980s to more than 32% in the 1990s and to 49% after 2000. The risk of herb‐drug interaction is therefore increasingly recognized as a public health problem. To the best of our knowledge, we report here the first case of interaction between ginger and anticancer drug, with serious consequences for the patient. There is an urgent need regarding complementary and alternative medicine: Both clinicians and patients should be aware of the potential interactions between herbs and prescribed drugs.